PEMANFAATAN COPEPODA Oithona sp SEBAGAI PAKAN HIDUP LARVA IKAN KERAPU - aliah, ratu siti; yaniharto, dedy (Jurnal Sains dan Teknologi Indonesia, 2010)
The key success of producing grouper seed depends on the availability of high and complete nutritive live food (zooplankton) during larvae development stage. Rotiferand Artemia are common zooplankton that has been used in most of grouper hatchery. The cysts of Artemia is expensive because it’s still imported, therefore potential zooplankton from Indonesians waters should be developed to replace or to substitute Artemia. Copepod Oithona sp can be found easily in Indonesian marine waters. Oithona sp can be developed to adult stage within 7 days. One female Oithona can produce 8 to 22 nauplii with average 14,39 ± 3,62 nauplii. The larva ofhumpback grouper (Cromileptes altivelis) fed by Oithona sp showed a higher DHA content (0,30 % b/b) than those fed by copepod + Artemia (0,15 % b/b) and and Artemia only (0,03 % b/b). The EPA content in larva fed by Oithona also showed thehighest, 0,30 % b/b. However, improvement technique of monoculture Oithona should be carried out due to mass mortality and contamination by protozoan and rotifer.